2021
DOI: 10.1097/jsm.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucocorticoids on Athletic Performance: A Systematic Review and Meta-Analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Depending on sport‐specific variables and amounts of glucocorticoids used, a growing body of evidence supports the position that this drug class indeed possesses the potential to enhance athletic performance. At the same time, glucocorticoids can cause harm to health in athletes, 108 and in consideration of a substantial amount of scientific and medical data, substance‐specific laboratory reporting levels as well as guidance as to washout periods following permissive and therapeutic drug use were presented in a comprehensive review by Ventura et al 105 A concept was created and applied where the upper range of the normal physiological daily cortisol production (26.4 mg) plus a 20% margin was taken into consideration, above which the cortisol‐equivalent resulting from synthetic glucocorticoid intake yields a continuum of increasing risk for performance enhancement. By means of published administration study data, reporting levels ranging from 15 to 300 ng/ml were suggested.…”
Section: Glucocorticoids and Cannabinoidsmentioning
confidence: 99%
“…Depending on sport‐specific variables and amounts of glucocorticoids used, a growing body of evidence supports the position that this drug class indeed possesses the potential to enhance athletic performance. At the same time, glucocorticoids can cause harm to health in athletes, 108 and in consideration of a substantial amount of scientific and medical data, substance‐specific laboratory reporting levels as well as guidance as to washout periods following permissive and therapeutic drug use were presented in a comprehensive review by Ventura et al 105 A concept was created and applied where the upper range of the normal physiological daily cortisol production (26.4 mg) plus a 20% margin was taken into consideration, above which the cortisol‐equivalent resulting from synthetic glucocorticoid intake yields a continuum of increasing risk for performance enhancement. By means of published administration study data, reporting levels ranging from 15 to 300 ng/ml were suggested.…”
Section: Glucocorticoids and Cannabinoidsmentioning
confidence: 99%